Locus of Scripture’s Authority in Calvin vis-à-vis His Opponents - John Jebaseelan (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2025)
Most of the doctrinal problems in Christendom spring from a faulty understanding of the nature and authority of the Scripture. When the nature of Scripture is misunderstood and its authority demeaned, the life of the Church and the theology suffers. History of theology is also the history of the quest to find the right understanding about Scripture because it is from this doctrine all other doctrines flow forth. Reformation is one exemplary movement in which this quest turned the history of the Church along with the western civilization upside down.  The nature of the authority of the Scripture and its relationship with other sources of the knowledge of God became the focal point of the reformation. The whole narrative of reformation hinged on the place given to Scripture in the theological discourse and the life of the Church. Reformers led the movement with the cry Sola Scriptura which means that the “Scripture remains the final authority” to decide anything concerning faith to Scripture. That is why when Luther was asked at Diet of Worms to retract the writings he had produced, he said, “I am bound by the Scriptures I have quoted and my conscience is captive to the Word of God. I cannot and I will not retract anything.” Reformers gave supreme and final authority to Scripture and all other sources only had relative authority.Among the reformers, Calvin’s view of Scripture is dynamic and practical which is the result of the constant dialogue with his opponents and their errant views. This paper would explore where Calvin locates the authority of the Scripture vis-à-vis his opponents – the Roman Catholic Church and the Radicals. In his struggle with his opponents he established a delicate balance between the Word of God and the Spirit of God in which the Word of God is inherently authoritative and the Spirit of God is the witness and seal to it. Evangelical theology needs to reclaim this balance to be true to the biblical witness in the contemporary world.